Libraries as Therapeutic Spaces for Supporting the Mental Health of Santri in Pesantren - Muhamad Abdul Muid; Adi Sucipto (Program Studi Bimbingan dan Konseling Islam, 2026)
The mental health of santri is influenced by academic demands, communal life, adjustment processes, social support, and spiritual experiences within pesantren. In this context, libraries may be developed not only as learning resource centres but also as therapeutic spaces that support the psychological and spiritual well-being of santri. This study aims to examine the role of libraries as therapeutic spaces in supporting santri mental health in pesantren. An integrative literature review was conducted on 58 Indonesian- and English-language publications issued between 2020 and 2026. The literature was analysed through thematic synthesis focusing on santri mental health, libraries as safe and restorative spaces, bibliotherapy, mental health information services, psychosocial support, and spiritual–psycho-Sufistic approaches. The findings indicate that therapeutic pesantren libraries can be conceptualised through five interconnected dimensions: physical-restorative, informational, bibliotherapeutic, social-relational, and spiritual–psycho-Sufistic. These dimensions are manifested through calm and comfortable spaces, access to credible mental health information, reflective reading activities, peer support, collaboration with counsellors and pesantren caregivers, and the integration of muhasabah, dhikr, sabr, shukr, tawakkul, and Sufi literature. The model positions libraries at three levels of support: universal-preventive support, targeted support, and a bridging function towards professional services. This review concludes that libraries can become part of the pesantren mental health ecosystem without assuming the clinical functions of qualified professionals.